Dossier débat : Moi, Daniel Blake - Valérie Cohen; François Sarfati; Jean-Marie Pillon; Claire Lefrançois; Sacha Leduc (La Nouvelle Revue du Travail)
Abstract : This paper focuses on the Ken Loach’s movie I, Daniel Blake. The film follows Daniel Blake as he tries to face with the british social system. How does filmmaker try to show the evolution of the unemployement system? How do sociologists try to explain the turn in the social protection system? What is the difference between the british filmmaker eye and the sociologist one? What is the difference between the situation in Great Britain and in France? And how close are British and French realities? These questions were asked to three sociologists, Jean-Marie Pillon, Claire Lefrançois, and Sacha Leduc. Their perspectives provide additional insight into the subject.